Uma melhoria no processo ágil da COTIC-PROEG da UFPA para atendimento do processo de desenvolvimento de requisitos do MR-MPS-SW - MONTEIRO, Lucas Tavares (2019)
Nowadays, many companies seek to improve their software process development, using quality models as its foundation. In this context, the Brazilian Software Process Improvement (MPS.BR), as well as the Software MPS Model (MR-MPS-SW), were created. Frequently, organizations face difficulties on developing software requirements for a software product, which is a crucial factor to guarantee the creation of high-quality software. This work proposes an improvement on the agile development process of COTIC-PROEG, using the Requirements Development (DRE) process, from the MR-MPS-SW quality model, as its foundation. To do so, was made the modeling of the COTIC present process, which was used to make an evaluation based on the evidences of it attending the DRE expected results, found in the Software Implementation Guide of maturity level D of MR-MPS-SW, and then proposed a new development process, in a way that all expected results are fulfilled.